Crime, Laws, and Legalization: Perceptions of Colorado Marijuana Dispensary Owners and Managers: - Ward, Kyle C. (Criminal justice policy review, 2019)
The legalization of recreational marijuana in Colorado has complicated the relationships between local, state, and federal governments. Such challenges have trickled down to proprietors, managers, and employees within the new billion-dollar industry. Dispensary owners and managers often must navigate the implementation of new laws and policies in how they operate their business. The current study surveyed marijuana dispensaries across Colorado to explore owners’ and managers’ perceptions of operating their business while considering federal banking laws and concerns with state laws conflicting with federal laws, particularly in context of the 2016 presidential election.